Health-2000: An Integrated Large-scale Expert System for the Hospital of the Future - Boyom, S. F.; Kwankam, S. Y.; Asoh, D. A.; Asaah, C.; Kengne, F. (Methods of Information in Medicine, 1997)
Decision making and management are problems which plague health systems in developing countries, particularly in Sub-Saharan Africa where there is significant waste of resources. The need goes beyond national health management information systems, to tools required in daily micromanagement of various components of the health system. This paper describes an integrated expert system, Health-2000, an information-oriented tool for acquiring, processing and disseminating medical knowledge, data and decisions in the hospital of the future. It integrates six essential features of the medical care environment: personnel management, patient management, medical diagnosis, laboratory management, propharmacy, and equipment management. Disease conditions covered are the major tropical diseases. An intelligent tutoring feature completes the package. Emphasis is placed on the graphical user interface to facilitate interactions between the user and the system, which is developed for PCs using Pascal, C, Clipper and Prolog.
Keywords: Expert System; Hospital Information System; Decision-Support System; Tropical Diseases; Knowledge Base